AKUNTABILITAS KINERJA APARATUR SIPIL NEGARA DALAM PENYELENGGARAAN PELAYANAN PUBLIK DI KANTOR KECAMATAN KAWANGKOAN KABUPATEN MINAHASA - Lumentah, Switry Varlein; Posumah, Johnny Hanny; Londa, Very (Sam Ratulangi University, 2018)
abstract: the condition of the implementation of public services is still faced with the government systemthat has not been effective and efficient and the quality of human resources apparatus not yet adequate.Based on the background of the problem, this study aims to find Accountability Performance of Civil StateApparatus in Public Service Implementation at Kawangkoan District Office of Minahasa Regency.The method used in this research is research method descriptive qualitative. To describe State Civil StateApparatus Performance Accountability in Public Service Implementation at Kawangkoan District Office ofMinahasa Regency. Collection techniques are conducted through: Observation, Interview, Document StudyThe results showed that each apparatus can perform and complete the tasks carefully, both the task ofreporting to the superior, as well as the task of service to the community, the way the officers work is inaccordance with SOP and Tupoksi respectively; Kawangkoan District Office Apparatus always do goodservice to society in discipline, good discipline in terms of time, nature or character, or discipline incommunicating.Keywords: Accountability, Performance, State Civil Service and Public Service